2007
DOI: 10.1111/j.1532-5415.2007.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Late‐Life Mortality in Older Jews Exposed to the Nazi Regime

Abstract: Israeli Jews who survived exposure to the Nazi regime are not at greater risk for death than the general population of Israeli Jews in later life. It is unclear whether these individuals represent a particularly resilient group or whether the risks of psychological trauma on mortality are mitigated over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Similar to previous investigations (Ayalon & Covinsky, 2007;Kahana et al, 2005;Landau & Litwin, 2000;Shmotkin et al, 2003;Stessman et al, 2008), older Holocaust survivors showed a general resilience alongside specific vulnerabilities. Thus, Holocaust survivors generally showed functioning at levels similar to comparison groups, especially on physical markers.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar to previous investigations (Ayalon & Covinsky, 2007;Kahana et al, 2005;Landau & Litwin, 2000;Shmotkin et al, 2003;Stessman et al, 2008), older Holocaust survivors showed a general resilience alongside specific vulnerabilities. Thus, Holocaust survivors generally showed functioning at levels similar to comparison groups, especially on physical markers.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, CC survivors were found to be an especially resilient group when mortality risk was examined. Similarly to previous survival analyses (e.g., Ayalon & Covinsky, 2007), the younger cohort of CC survivors in the IMAS demonstrated a similar mortality risk to all other groups. However, the older cohort of CC survivors in the CALAS showed a lower mortality risk compared to exposed survivors and postwar immigrants.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Most pertinent to the queries raised above is the study of Holocaust survivors, since it concerns survivors of massive trauma, a large part of whom are presently moving from old to old-old age. Holocaust survivors living in the community demonstrate a general resilience, but also specific vulnerabilities (Ayalon & Covinsky, 2007;Kahana, Harel, & Kahana, 2005;Shemesh, Levav, Radomislensky, & Brodsky, in press;Shmotkin, Blumstein, & Modan, 2003;Stessman et al, 2008). This balance of resilience and vulnerability is reflected in, as well as derived from, positive and negative features in the survivors' life narratives (Cohen & Shmotkin, 2007;Shmotkin & Shrira, in press).…”
Section: Conflicting Expectations Regarding the Life Story Of Old-oldmentioning
confidence: 95%